Microorganisms Producing Biosurfactant Selection and Characterization of New Discovered Bioemulsifier that will be Used to Create Ecological Heating Production Technology (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The chemical synthesis of surface active compounds is economically inefficient. It requires much energy expense, raw materials and harmful reagents. Biological biosynthesis of surface active substances happens in milder conditions without the use of dangerous chemical reagents. The main goal of this work was to select a microorganism strain capable of producing a bioemulsifier with an ability to create a stable water / fuel-oil emulsion that could be used to design a new ecological heating technology. To this end, 3 microorganism strains displaying a high emulsification activity were used. The new discovered surface active substance (SAS) was investigated with different methods (hydrocarbon overlay agar method, emulsification activity determination, microscopic observation). The production of bioemulsifier (BE) was studied by using soluble and insoluble carbon sources. It was found that Arthrobacter sp. Pr82 is the best bioemulsifier producer. Oleic acid was ascertained as the best carbon source for the production of discovered BE.